A caminho de Westeros: Game of thrones - a complexidade narrativa na série televisiva e seu desenvolvimento nas demais mídias - JESUS, Katia de (2015)
This dissertation has as central focus the analysis of the television series Game of Thrones. Its main objective is, through exploratory and qualitative research, how to analyze the narrative complexity is built and developed in the television series and what its relationship with other media or products with their theme. It is intended, therefore, check the role played by these media in the narrative complexity of the TV series. To achieve the proposed objective, the survey was structured on a theoretical framework, the authors as Umberto Eco (1989), Omar Calabrese (1987), Maria Cristina Costa (2000), Arlindo Machado (2000), Marcelo Bulhões (2009), Cássio Starling Carlos (2006), Henry Jenkins (2009), Jason Mittell (2012), Jean-Pierre Esquenazi (2010), Carlos A. Scolari (2013), Renata Pallottini (1998), Jak Boumans (2005), Gaby Allrath and Marion Gymnich (2005), among others. The structure of the dissertation includes a reflection on the aspects related to contemporary television serial narratives, presenting the fictional universe of Game of Thrones and finally the analysis of the television series and the other media that surround it. Game of Thrones is an example of contemporary television serial narratives and how the narrative complexity can be developed in the series and other current media.